PENGARUH SARAPAN PAGI TERHADAP KONSENTRASI DAN HASIL BELAJAR PKN PESERTA DIDIK KELAS 5 GUGUS SRIKANDI KECAMATAN GUNUNGPATI KOTA SEMARANG - Haniah, Aryan Hasna; Witanto, Yuli (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The aim of this research is to determine the effect of breakfast on the concentration and learning outcomes of class 5 students in the Srikandi cluster, Gunungpati sub-district, and Semarang city. The method used ia a quantitative approach based on facts. This research technique uses a questionnaire and documentation in the form of learning outcomes. The subjects of this research were 124 students in the Srikandi cluster, Gunungpati sub-district, and Semarang city. The research data shows H01, H02, and H03 were rejected because the significance value was greater than the research critical limit, namely 0,05. And Ha1, Ha2, and Ha3 were accepted because the significance value was less than the research critical limit, namely 0,05. Si it can be concluded that there is a significant impact of breakfast on the concentration and learning outcome of class 5 students in the Srikandi group, Gunungpati sub-district, and Semarang city.